A Syntactic Analysis of Noun Phrase through “Hansel and Gretel” Short Story To 1st Semester of Accounting Students at University of Bina Sarana Informatika - Paramita Kusumawardhani; Ani Rakhmanita (International Journal of English and Applied Linguistics (IJEAL), 2022)
Languages all over the world have their own grammar for constructing words and their components. The aim of the research is to recognize, classify and analyze noun phrases by reading Hansel and Gretel short story. A noun phrase is a part of the syntax. The syntax is a part of Linguistics. It has meaningful elements together to form words, words together to form phrases, phrases together to form clauses, clauses together to form sentences, and sentences together to form texts. Noun phrase has some aspects; they are identifier, adjective, noun modifier, quantifier, preposition phrase, participle clause, conjunctions, and indefinite clause. Hansel and Gretel short story was used as the research instrument about noun phrases. The method used to do the research was descriptive qualitative. The participants of this research are the 1st semester of accounting students at the University of Bina Sarana Informatika. The results of this research are: there are 25 noun phrases, 16 noun phrases are about rules 1, determiner + headword, meanwhile 9 other noun phrases are about common noun phrase, found in Hansel and Gretel short story.